THE HIALINE PROJECT: ALLERGEN RELEASE FROM POLLEN ACROSS 10 EUROPEAN COUNTRIES - Buters, J.M. (2010)
Exposure to allergens is one of severa1 factors determining sensitization and allergic symptoms in individuals. Exposure to aeroallergens from pollen is assessed by counting allergenic pollen in ambient air. However, proof is lacking that pollen count is representative for allergen exposure. We therefore monitored simultaneously birch, grass and olive pollen counts and their corresponding major pollen allergens Bet v 1, Phl p 5 and Ole e 1 across Europe. Already at one location in Europe in Munich, Germany, it has been found that the same amount of pollen from different years, different trees and even different days released up to lO-fold different amounts of Bet v 1. Thus exposure to allergen is poorly monitored by only monitoring pollen countl-2. Monitoring the allergen itself in ambient air might be an improvement in allergen exposure assessment. The objective of the HIALINE-project is to evaluate if these effects found in Munich, Germany are also measurable over a bigger geographic area like Europe, and at the same time implement an outdoor allergen early warning network, in addition to the pollen forecasts. Climatic factors that influence allergen exposure will be extracted and will be used to calculate the effect of climate change on local airborne allergen exposure. The major allergens from the top 3 airborne allergens in Europe (grasses, birch and olive) are sampled with a cascade impactor, extracted and analyzed by allergen specific ELISA 's. Pollen counts are measured by standard pollen traps and correlated with the weather data. Allergen forecast will be calculated by incorporating the SILAM chemical transport model and compared with the observations of HIALINE aiming at a comprehensive parameterization of the allergen release and transport. Expected outcomes are the implementation of a network of European outdoor allergen measurements to better predict allergic symptoms. Also the climatic factors that govern allergen exposure in outdoor air will be established. These can be used to calculate the effect of climate change on the health effects of airborne allergens The research leading to these results has received funding from the Executive Agency for Health and Consumers under grant agreement No 2008 11 07.